Nutritional metabolism and cerebral bioenergetics in Alzheimer's disease and related dementias. Issue 3 (8th December 2022) - Yassine, Hussein N.; Self, Wade; Kerman, Bilal E.; Santoni, Giulia; Navalpur Shanmugam, NandaKumar; Abdullah, Laila; Golden, Lesley R.; Fonteh, Alfred N.; Harrington, Michael G.; Gräff, Johannes; Gibson, Gary E.; Kalaria, Raj; et al.
Abstract: Disturbances in the brain's capacity to meet its energy demand increase the risk of synaptic loss, neurodegeneration, and cognitive decline. Nutritional and metabolic interventions that target metabolic pathways combined with diagnostics to identify deficits in cerebral bioenergetics may therefore offer novel therapeutic potential for Alzheimer's disease (AD) prevention and management. Many diet‐derived natural bioactive components can govern cellular energy metabolism but their effects on brain aging are not clear. This review examines how nutritional metabolism can regulate brain bioenergetics and mitigate AD risk. We focus on leading mechanisms of cerebral bioenergetic breakdown in the aging brain at the cellular level, as well as the putative causes and consequences of disturbed bioenergetics, particularly at the blood‐brain barrier with implications for nutrient brain delivery and nutritional interventions. Novel therapeutic nutrition approaches including diet patterns are provided, integrating studies of the gut microbiome, neuroimaging, and other biomarkers to guide future personalized nutritional interventions.